Business Education in the 21st Century : Examining the Antecedents and Consequences of Student Team Virtuality : Final Report. - Kavanagh, Marie; Sargent, Leisa; Caspersz, Donella; Levak, Natasha (Office for Learning and Teaching, 2012)
Final report from a project that investigated the need to train students to be able to work effectively in teams, particularly virtual teams. The project was both research-driven and experience-based and considered the concept of 'virtuality' in teaching and learning at university. Virtuality for the purpose of this project referred to online collaboration by team members without the constraints of time and the necessity to be in the same place. The project sought to establish how to: design online resources to facilitate implementation of virtual student teams; select appropriate technologies to support virtual student team activities; provide online training for staff and students to assess readiness; enhance the effectiveness of virtual teamwork; evaluate virtual student team projects in the Australian business education context.